Rapid prototyping : principles and applications - Noorani, Rafiq, ....- (Hoboken : Wiley, 2006)
Introduction 2 Principles of rapid prototyping 3 Liquid-based RP systems 4 Solid-based RP systems 5 Powder-based RP systems 6 Materials for rapid prototyping 7 Reverse engineering 8 Rapid tooling 9 Medical applications in rapid prototyping 10 Industry perspectives 11 Research and development App. A RP resources App. B Worldwide RP system manufacturers App. C Rapid tooling technology suppliers App. D RP software developers App. E RP material suppliers
Keywords: Rapid prototyping